Does the temporal cortex make us human? A review of structural and functional diversity of the primate temporal lobe - Braunsdorf, M; Freches, GB; Roumazeilles, L; Eichert, N; Schurz, M; Uithol, S; Bryant, KL; Mars, RB (Elsevier, 2021)
Temporal cortex is a primate specialization that shows considerable variation in size, morphology, and connectivity across species. Human temporal cortex is involved in many behaviors that are considered especially well developed in humans, including semantic processing, language, and theory of mind. Here, we ask whether the involvement of temporal cortex in these behaviors can be explained in the context of the ‘general’ primate organization of the temporal lobe or whether the human temporal lobe contains unique specializations indicative of a ‘step change’ in the lineage leading to modern humans. We propose that many human behaviors can be explained as elaborations of temporal cortex functions observed in other primates. However, changes in temporal lobe white matter suggest increased integration of information within temporal cortex and between posterior temporal cortex and other association areas, which likely enable behaviors not possible in other species.